2013
DOI: 10.1021/am402919f
|View full text |Cite
|
Sign up to set email alerts
|

In/Ga-Free, Inkjet-Printed Charge Transfer Doping for Solution-Processed ZnO

Seong Hun Yu,
Beom Joon Kim,
Moon Sung Kang
et al.

Abstract: An In/Ga-free doping method of zinc oxide (ZnO) is demonstrated utilizing a printable charge transfer doping layer (CTDL) based on (3-aminopropyl)triethoxysilane (APS) molecules. The self-assembled APS molecules placed on top of ZnO thin films lead to n-type doping of ZnO and filling shallow electron traps, due to the strong electron-donating characteristics of the amine group in APS molecules. The CTDL doping can tune the threshold voltage and the mobility of the ZnO thin-film transistors (TFTs) as one varies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
0
28
1
Order By: Relevance
“…Finally, it is noteworthy that our findings for the 15 nm‐thick ZnO are in contradiction to the previously reported results presented by Yu et al who proposed a charge transfer doping effect through the use of self‐assembled monolayers (SAMs) . In the latter study it was suggested that the doping effect vanishes at a ZnO thickness of ≈8 nm, whereas in our 15 nm‐thick ZnO the doping effect is still visible.…”
contrasting
confidence: 99%
“…Finally, it is noteworthy that our findings for the 15 nm‐thick ZnO are in contradiction to the previously reported results presented by Yu et al who proposed a charge transfer doping effect through the use of self‐assembled monolayers (SAMs) . In the latter study it was suggested that the doping effect vanishes at a ZnO thickness of ≈8 nm, whereas in our 15 nm‐thick ZnO the doping effect is still visible.…”
contrasting
confidence: 99%
“…While ZnO films comprising nanocrystals have been made [9][10][11][12] , achieving high electron mobility without gating has been elusive. We form thin films comprising these nanocrystals by supersonic expansion and subsequent impaction of the plasma effluent containing the nanocrystals onto suitable substrates.…”
mentioning
confidence: 99%
“…Currently, the sputtered and sol-gel amorphous indium-gallium-zinc oxide (a-IGZO) TFTs have a typical effective mobility in the range of 10-40 cm 2 /Vs and 1-14 cm 2 /Vs, respectively. 3,[5][6][7][8] Together with a large energy bandgap (> 3eV) to enable the transparency property, AOS TFTs are promising for developing flexible and transparent electronic devices. [9][10][11] Current developments of AOS TFTs have been focused on increasing the effective mobility, i.e.…”
mentioning
confidence: 99%